Thursday
March 23, 2017

Post a New Question

Posted by on Saturday, December 17, 2011 at 6:47pm.

Prove that the equation is an identity:

cot4theta - csc4theta = -cot sq theta - csc sq theta

How ??

  • Trig - , Saturday, December 17, 2011 at 11:41pm

    cot^4 - csc^4
    = (cot^2 - csc^2)(cot^2 + csc^2)
    = (-1)(cot^2 + csc^2)
    = -cot^2 - csc^2

    remember csc^2 = 1 + cot^2 ??

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question